Maximising the health impacts of free advice services in the UK: A mixed methods systematic review. (21st March 2022) - Young, David; Bates, Geoff
Abstract: After a decade of austerity spending cuts and welfare reform, the COVID‐19 pandemic has posed further challenges to the finances, health and wellbeing of working‐age, low‐income people. While advice services have been widely seen (and funded) as an income maximisation intervention, their health and well‐being impact is less clear. Previous systematic reviews investigating the link between advice services and health outcomes have found a weak evidence base and cover the period up until 2010. This mixed methods review examined up to date evidence to help understand the health impacts of free and independent welfare rights advice services. We included evaluations of free to access advice services on social welfare issues for members of the public that included health outcomes. Through comprehensive searches of two bibliographic databases and websites of relevant organisations we identified 15 articles based on a mixture of study designs. The advice interventions evaluated were based in a range of settings and only limited information was available on the delivery and nature of advice offered. We undertook a convergent synthesis to analyse data on the effectiveness of advice services on health outcomes and to explain variation in these outcomes. Our synthesis suggested that improvements in mental health and well‐being measures are commonly attributed to advice service interventions. However, there is little insight to explain these impacts or to inform the delivery of services that maximise health benefits. Co‐locating services in health settings appears promising and embracing models of delivery that promote collaboration between organisations tackling the social determinants of health may help to address the inherent complexities in the delivery of advice services and client needs. We make recommendations to improve routine monitoring and reporting by advice services, and methods of evaluation that will better account for complexity and context.